"Nothing Good Ever Came from New Jersey": Expectations and the Sensory Perception of Wines*. (24th October 2014) - Ashton, Robert H.
Abstract The influence of expectations on the sensory perception of wines is investigated in three studies in which New Jersey and California red wines are blind tasted. Studies 1 and 2, in which only the color of the wines is known prior to tasting, demonstrate that neither wine club members nor experienced wine professionals can distinguish between New Jersey and California wines in terms of personal enjoyment. In contrast, Study 3, in which tasters are informed that some (though not which) of the wines are from New Jersey, finds that when a wine is believed to be from New Jersey it receives lower enjoyment ratings than when the identical wine is believed to be from California—regardless of whether the wine is actually from New Jersey or California. The results enhance our understanding of the role of expectations in the interpretation of subjective experiences. Implications for wine producers and wine consumers are explored. (JEL Classification: C91)